RE-READ THE PROSTITUTION PREVENTION POLICY IN BALI: BIO-POLITICS IN POWER RELATIONS OF THE REGIONAL BUREAUCRATES AND SEX WORKERS IN THE DENPASAR CITY - Wijaya, Komang Adi Sastra; Erviantono, Tedi (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
The prostitution prevention policy in eastern culture country such as Indonesia tends to be approached by eliminating the commercial sex workers (CSWs) due to the social moral and health reasons or by alleviating them by providing business capital for their welfare. This policy is always re-reviewed by both the central and the regional government. They ignore whether the acts of prostitution they repress are able to create a space so that as if the state allows them. The state through the regional bureaucratic apparatus always holds routine actions of closing the prostitution business and bringing CSWs into order with a purpose to improve the moral image of the regional leaders along with the bureaucratic apparatus. This article tries to re-read the regulations related to the prevention of prostitution in Bali, especially the Denpasar city. This does not review the successful narrative of the implementation of The Regional Regulation No. 1 of 2015 concerning Public Order which is always reported by the bureaucracy, but it re-reads the regulation by examining various stories of potential failures of this product of regulation, the contention of discourse as well as the state’s hidden agenda which actually becomes a productive power unrealized by either the regulatory enforcer bureaucrats or the object of the regulation namely the CSWs. This article has a non-positivist paradigm with an interpretive perspective. The theory used in this article is governmentality especially bio-power and the Michel Foucault’s panopticon concept borrowed from Bentham’s. This is a qualitative research with a case study in Denpasar. Denpasar is a city considered an actualization of urban space believed to always have a tug of war of the production of sexuality discourse. The data was collected by observation, interviews that prioritized emics rather than ethics, and documentation. The data were analyzed by using critical discourse analysis that examined the micro findings in the field and then analyzed the structure of the macro politics therein.